KELAYAKAN BAHAN AJAR INTERAKTIF E-MODUL PEMBELAJARAN KIMIA PADA MATERI KOLOID BERBASIS KEARIFAN LOKAL PAPUA - Kelana, Ardian Hangga; Irawan, Sakka; Karubaba, Marice; Sahar, Adnan (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aims to determine the feasibility of interactive e-module chemistry teaching materials on colloid material based on Papuan local wisdom. The research method used is Research and Development (R and D). The research sample was conducted in class XI IPA 1 SMA YPK Diaspora Kotaraja Jayapura with a total of 30 students. The results of the study indicate that: the feasibility of interactive e-module chemistry teaching materials on colloid material based on Papuan local wisdom based on material validators obtained an average of 88% with the category "Very Valid/Very Practical", media validators obtained an average of 89% with the category "Very Valid/Very Practical", student responses in limited scale trials obtained an average of 90% with the category "Very Feasible", student responses in large scale trials obtained an average of 87% with the category "Very Feasible", and chemistry subject teacher responses obtained an average of 83% with the category "Very Feasible". The recapitulation of the value of the feasibility aspect of interactive e-module chemistry teaching materials on colloid material based on Papuan local wisdom is 87% with the category "Very Feasible" for use in schools. ABSTRAKPenelitian ini bertujuan untuk mengetahui kelayakan bahan ajar interaktif e-modul pembelajaran kimia pada materi koloid berbasis kearifan lokal Papua. Metode penelitian menggunakan Research and Development (R and D). Sampel penelitian dilaksanakan di kelas XI IPA 1 SMA YPK Diaspora Kotaraja Jayapura dengan jumlah 30 peserta didik. Hasil penelitian menunjukkan bahwa: kelayakan bahan ajar interaktif e-modul pembelajaran kimia pada materi koloid berbasis kearifan lokal Papua berdasarkan validator materi memperoleh rerata sebesar 88% dengan kategori “Sangat Valid/Sangat Praktis”, validator media memperoleh rerata sebesar 89% dengan kategori “Sangat Valid/Sangat Praktis”, respons peserta didik uji skala terbatas memperoleh rerata sebesar 90% dengan kategori “Sangat Layak”, respons peserta didik uji skala luas memperoleh rerata sebesar 87% dengan kategori “Sangat Layak”, dan respons guru mata pelajaran kimia memperoleh rerata sebesar 83% dengan kategori “Sangat Layak”. Hasil rekapitulasi nilai aspek kelayakan bahan ajar interaktif e-modul pembelajaran kimia pada materi koloid berbasis kearifan lokal Papua sebesar 87% dengan kategori “Sangat Layak” digunakan di sekolah.